The psychological dynamics of premeditated murder offenders: A case study of adult male inmates at correctional institution X - Wilona, Jessica Shirleen; Yuliandari, Elly (University of Merdeka Malang, 2025)
Homicide is a phenomenon that threatens public safety and security, understanding the factors that causes this crime is an important step towards prevention. This study aims to describe the psychological dynamics of a premeditated murder perpetrator using a qualitative approach and case study design. The subject was an inmate in Prison X. Data were collected through interviews and psychological assessments, including graphic tests (BAUM, DAP, HTP, and WZT), the Rorschach, the Hare Psychopathy Checklist, and the SPM test. The results shows that the murder was influenced by predisposing factors such as an underdeveloped ego, aggression and impulsivity leading to maladaptive emotion regulation, emotional sensitivity and instability, anxiety related to close relationships, inappropriate internalization of norms and values, limited intellectual capacity and interests, and a tendency to suppress, ignore, and eliminate discomfort and its triggering stimuli — patterns developed from neglectful parenting and early unmet needs for love. The precipitating factors are being included in a community that encouraged aggression, and the wife’s infidelity as the emotional trigger.